2008
DOI: 10.1021/es801010e
|View full text |Cite
|
Sign up to set email alerts
|

Up-Cycling of PET (Polyethylene Terephthalate) to the Biodegradable Plastic PHA (Polyhydroxyalkanoate)

Abstract: The conversion of the petrochemical polymer polyethylene terephthalate (PET) to a biodegradable plastic polyhydroxyal-kanoate (PHA) is described here. PET was pyrolised at 450 degrees C resulting in the production of a solid, liquid, and gaseous fraction. The liquid and gaseous fractions were burnt for energy recovery, whereas the solid fraction terephthalic acid (TA) was used as the feedstock for bacterial production of PHA. Strains previously reported to grow on TA were unable to accumulate PHA. We therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
142
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(146 citation statements)
references
References 37 publications
2
142
2
Order By: Relevance
“…Pseudomonads are also well-known for their bioremediation properties including the biodegradation recalcitrant and/or toxic aromatic carbon substrates [98], and have been successfully applied in the treatment of contaminated effluents, exhaust gas and soils [99][100][101]. Recent studies demonstrated that aromatic-degraders P. putida F1 (DSM 6899), P. putida mt-2 (NCIMB 10432), and P. putida CA-3 (NCIMB 41162) could bioconvert toxic pollutants benzene, toluene, ethylbenzene, xylene (BTEX) and styrene to mcl-PHA [86] [76,77,80], which offers the potential benefit to off-set waste treatment cost through PHA recovery.…”
Section: Gram-negative Bacteriamentioning
confidence: 99%
“…Pseudomonads are also well-known for their bioremediation properties including the biodegradation recalcitrant and/or toxic aromatic carbon substrates [98], and have been successfully applied in the treatment of contaminated effluents, exhaust gas and soils [99][100][101]. Recent studies demonstrated that aromatic-degraders P. putida F1 (DSM 6899), P. putida mt-2 (NCIMB 10432), and P. putida CA-3 (NCIMB 41162) could bioconvert toxic pollutants benzene, toluene, ethylbenzene, xylene (BTEX) and styrene to mcl-PHA [86] [76,77,80], which offers the potential benefit to off-set waste treatment cost through PHA recovery.…”
Section: Gram-negative Bacteriamentioning
confidence: 99%
“…Pseudomonas putida GO16 was grown on MSM medium supplemented with sodium terephthalate (TA) (1.95 g carbon L -1 ) and solidified with 15 g L -1 agar as it grew poorly on PIA. TA was used as a selective carbon source, to lower the risk or contamination by other bacterial strains, as P. putida GO16 was originally isolated using this carbon source 54 Growth conditions for PHA accumulation in shaken flask cultures Growth experiments were carried out in 250 mL Erlenmeyer flasks containing 50 mL of nitrogen-limited MSM medium supplemented with the appropriate carbon source at a concentration of 3 g L -1 . Ammonium chloride in this medium was limited to 0.25 g L -1…”
Section: Bacterial Growth Medium and Strain Maintenancementioning
confidence: 99%
“…Sample concentration of 1 % (w/v) and injection volumes of 500 µL were used. A molecular weight calibration curve was generated with polystyrene standards with low polydispersity 31 . Differential scanning calorimetry (DSC).…”
Section: Gel Permeation Chromatography (Gpc)mentioning
confidence: 99%
See 1 more Smart Citation
“…The microbes in O'Connor's study (8), which the scientists isolated from soil exposed to PET granules, use the TA, composed of carbon, hydrogen, and oxygen, to string together monomers of 3-hydroxydecanoic acid into PHA. That technology has been spun out into a company called Bioplastech Ltd., in Dublin, which has taken on the major challenges of scaling up the technology and making it economically competitive.…”
Section: Chemical Recyclingmentioning
confidence: 99%